Climate change and health: what's the problem? - Anstey, Matthew (2013)
The scientific consensus is that global warming is occurring and is largely the result of greenhouse gas emissions from human activity. This paper examines the health implications of global warming, the current socio-political attitudes towards action on climate change and highlight the health co-benefits of reducing greenhouse gas emissions. In addition, policy development for climate change and health should embrace health systems strengthening, commencing by incorporating climate change targets into Millennium Development Goal 7.